Advancements in research on transcutaneous electrical acupoint stimulation for alleviating pelvic pain in women - Rong Zhang; Yi Ling Wang; Xin Lei Lu; Shang Wang; Xiao Hong Chang; Hong Lan Zhu (Gynecology and Obstetrics Clinical Medicine)
Background Pelvic pain is a common complaint of discomfort in women, with an increasing incidence and seriously affecting patients’ quality of life. Its etiology involves multiple systems and disciplines, and therefore treatment modalities are diverse. Transcutaneous electrical acupoint stimulation (TEAS) therapy is a classic analgesic means, and electrical stimulation of local acupoints can achieve obvious analgesic effects. This review aims to discuss the application of TEAS for the treatment of various types of pelvic pain, the selection of optimal parameters and the renewal of equipment.Method Result TEAS for treatment of pelvic pain in women has been reported mainly for endometriosis, pelvic inflammatory disease (PID), intrauterine adhesion (IUA), pelvic stasis syndrome, interstitial cystitis, primary dysmenorrhoea and other diseases. And for parameter selection, the most used of frequency is dilatational wave, the most used stimulation intensity is 10–20 mA, and the acupoint selection should be based on the specific conditions of the patient.Conclusions The analgesic mechanism of TEAS has not been fully elucidated, but the efficacy of the treatment is remarkable and there are no significant adverse effects. The selection of the parameters for TEAS and the combination of acupoints for different pains are still the main directions of future research.